2015
DOI: 10.1039/c4nr07139e
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stimuli responsive Cu2S nanocrystals as trimodal imaging and synergistic chemo-photothermal therapy agents

Abstract: A size and shape tuned, multifunctional metal chalcogenide, Cu2S-based nanotheranostic agent is developed for trimodal imaging and multimodal therapeutics against brain cancer cells. This theranostic agent was highly efficient in optical, photoacoustic and x-ray contrast imaging systems. The folate targeted, NIR-responsive photothermal ablation in synergism with the chemotherapeutic action of doxorubicin proved to be a rapid precision guided cancer-killing module. The multi-stimuli, i.e., pH-, thermo- and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…Hydrophilicity of the NCs is a principally crucial aspect when considering a nanomaterial for biological applications. To address this issue, a biofunctionalization, utilizing lipid-PEG hybrids to cap the NCs via a simple thin film hydration technique was employed 21 . The NCs were desiccated completely with lipid-PEG resulting in a thin film, which was further hydrated using PBS, yielding lipid-PEG coated NCs (PEG-NCs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophilicity of the NCs is a principally crucial aspect when considering a nanomaterial for biological applications. To address this issue, a biofunctionalization, utilizing lipid-PEG hybrids to cap the NCs via a simple thin film hydration technique was employed 21 . The NCs were desiccated completely with lipid-PEG resulting in a thin film, which was further hydrated using PBS, yielding lipid-PEG coated NCs (PEG-NCs).…”
Section: Resultsmentioning
confidence: 99%
“…Inorganic nanoparticles as gold, metal sulfides etc., hold high-extinction coefficients in converting near-infrared (NIR) light to heat, and have been examined for photothermal therapy. Due to their tunable surface plasmon and NIR-thermal responsiveness, copper based chalcogenides seem promising in a wide range of biomedical applications and are ideally suited for theranostics 20 21 22 . Being p-type semiconductors, copper based chalcogenides determine charge transport and provide a composition-dependent localized surface plasmon resonance (LSPR) in the near-infrared (NIR) region 23 24 25 26 .…”
mentioning
confidence: 99%
“…To date, there are various combined treatment approaches were developed 4-10. Among them, the combination of PTT and chemotherapeutic agents shows the most promising prospect to optimize cancer therapy 5, 11-13.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of the plasmonic semiconductor copper chalcogenide (Cu 2-x Y) nanocrystals is the tunable optical properties by varying value of x in a wide range between 0 and 1, from the Cu-rich Cu 2 S (chalcocite) to CuS (covellite). [32][33][34][35][36][37] For example, Burda and his co-workers found that the blue-shift of the absorbance spectra in NIR region occurred with the increase of free carrier concentration in different nonstoichiometric Cu 2-x S crystal phrases. [32][33][34][35][36][37] For example, Burda and his co-workers found that the blue-shift of the absorbance spectra in NIR region occurred with the increase of free carrier concentration in different nonstoichiometric Cu 2-x S crystal phrases.…”
Section: Introductionmentioning
confidence: 99%